Reorienting fiscal policy after the great recession - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2012)
The paper evaluates the fiscal policy initiatives during the Great Recession in the United States. It argues that, although the nonconventional fiscal policies targeted at the financial sector dwarfed the conventional countercyclical stabilization efforts directed toward the real sector, the relatively disappointing impact on employment was a result of misdirected funding priorities combined with an exclusive and ill-advised focus on the output gap rather than on the employment gap. The paper argues further that conventional pump-priming policies are incapable of closing this employment gap. In order to tackle the formidable labor market challenges observed in the United States over the last few decades, policy could benefit from a fundamental reorientation away from trickle-down Keynesianism and toward what is termed here a bottom-up approach to fiscal policy. This approach also reconsiders the nature of countercyclical government stabilizers.
Keywords: E24; E25; E61; E62; E65; H1; H5; J2; J6; J48; 330; Fiscal Policy; American Recovery and Reinvestment Act of 2009; Trickle-Down Keynesianism; Countercyclical Employment Policy